Computational fluid dynamics simulation of cryogenic safety analysis in an liquefied natural gas powered ship during liquefied natural gas leakage - Wang, Zhaowen; Zhang, Qipeng; Wang, Yi; Li, Xin; Zhou, Jiong (Frontiers in Energy Research, 2023)
LNG is considered a promising alternative fuel for the marine industry with the increasingly strict environmental requirements while the safety problems caused by LNG leakage accidents need to be concerned and analyzed. In this article, the cryogenic safety analysis of the fuel gas preparation room in an LNG-powered ship during LNG leakage accidents was performed by CFD simulations. The simulation results showed as follows: the range of cryogenic region in the fuel gas preparation room was related to flow field direction during LNG leakage; The surface temperature of equipment dropped to some extent during LNG leakage accidents. The temperature drop was less than 15 ℃, which was confirmed to be a safe temperature range in engineering; In addition, for safety operation analysis, the NG distribution situation of dangerous regions with explosive limit was also obtained.